Fecal sludge treatment for resource recovery and biological hazard control: Phase partitioning, process intensification, and data-driven optimization - Xiaoyu Cai; Jialiang Gu; Yitian Li; Jun Nan; Defeng Xing (Chemical Engineering Journal, 2026)

Collision avoidance for unmanned surface vehicle in busy waterways based on improved DDPG and IMMKF - Te Lian; Qijun Liu; Defeng Wu; Yuqin Li; Chunxin Tian (Ocean Engineering, 2026)

Corrigendum to “Linking microbial functional partitioning with methane productivity and stability in microbial electrolysis cell–anaerobic digestion hybrid systems” [Bioresour. Technol. 453 (2026) 134629] - Xue-Ting Wang; Yanxue Li; Yuxin Pan; Xue Xing; Bo Wang; Defeng Xing; Jun Nan; Jonathan Tian En Lee; Eakalak Khan; Daniel C.W. Tsang; Nan-Qi Ren; Yong Sik Ok (Bioresource Technology, 2026)

Flotation mechanism of an amide-based fatty acid collector for quartz ore: A gene-matching perspective - Wenda Guo; Baida Chen; Zhenyue Zhang; Sicheng Li; Han Zhang; Heng Zhang; Hanjun Wu; Defeng Liu (Minerals Engineering, 2026)

Cobalamin-autonomous Trichlorobacter facilitates robust In situ bioremediation of halogenated solvents - Xuhao Wang; Hengyi Liao; Xin Wang; Yuanzhi Wang; Defeng Li; Honglin Ma; Jiaojiao Yang; Xinyue Qian; Hongyan Wang; Qingyu Li; Zongming Xiu; Yi Yang (Journal of Hazardous Materials, 2026)

Chiglitazar alleviates cognitive dysfunction in diabetic mice by restoring mitochondrial function via the PPARs/Nrf2 signaling pathway - Junfang Yuan; Yuzhong Wang; Defeng Wang; Yanfeng Zhen; Yanan Sun; Li Wang; Hui Fang (Metabolic Brain Disease, 2026)

Alfalfa polysaccharides-driven Kineothrix alysoides alleviates deoxynivalenol-induced intestinal injury by regulating macrophage polarization - Shouren Li; Zhaoyang Li; Congbin Chen; Mengqi Liu; Yalei Cui; Xiaoyan Zhu; Zhichang Wang; Hao Sun; Defeng Li; Boshuai Liu; Yinghua Shi (Journal of Hazardous Materials, 2026)

Phthalate esters in cooking organic aerosols from various edible oils - Xiaolei Yang; Shuhui Xue; Qingpeng Meng; Siqi Tang; Chunlin Li; Lina Wang; Defeng Zhao (Journal of Environmental Sciences, 2026)

Linking microbial functional partitioning with methane productivity and stability in microbial electrolysis cell–anaerobic digestion hybrid systems - Xue-Ting Wang; Yanxue Li; Yuxin Pan; Xue Xing; Bo Wang; Defeng Xing; Jun Nan; Jonathan Tian En Lee; Eakalak Khan; Daniel C.W. Tsang; Nan-Qi Ren; Yong Sik Ok (Bioresource Technology, 2026)

Evaluation of an Automated Vaccination Strategy Against Aeromonas hydrophila in Grass Carp: A Comparative Study with Conventional Manual Injection - Lin Luo; Zhen Qin; Chen Li; Defeng Zhang; Yan Ren; Qing Wang; Jian Zhao; Songming Zhu; Zhangying Ye (Fishes, 2026)
(1) Background: Vaccination is crucial for Ctenopharyngodon idella, yet the impact of delivery methods on welfare and immunity requires investigation. (2) Methods: This study compared manual (HI-V) and automated (AI-V) injections of inactivated Aeromonas hydrophila vaccine. (3) Results: Both methods induced protective immunity, with AI-V achieving a slightly higher Relative Percent Survival (41.67%) than HI-V (37.84%). AI-V promoted stable erythropoiesis and robust systemic/mucosal IgM responses with elevated HSP70 and IL-6. Conversely, HI-V triggered sharp transient stress and upregulated Gadd45γ, indicating greater genotoxic stress. (4) Conclusions: Automated injection offers comparable immune protection with reduced physiological stress and improved homeostasis, supporting its use for welfare-conscious aquaculture.

A dynamic ray-tracing channel model for offshore unmanned surface vehicles integrated with marine vessel dynamics - Yao Sun; Wanli Tu; Defeng Wu; Yuqin Li; Siqin Wang (Ocean Engineering, 2026)

Effects of nanozyme on environmental fate and dissemination of antibiotic resistance genes in anaerobically digested sludge - Jing Wang; Peng Li; Ningyu Gao; Jun Ma; Defeng Xing (Bioresource Technology, 2026)

Identification of Gibberellin-mediated Key Genes for Salt Tolerance in Alfalfa Based on Transcriptomic Analysis - Guomin Li; Xiangling Ren; Wenxuan Zhu; Yingao Li; Zirui Liu; Xi Wang; Defeng Li; Yinghua Shi; Xiaoyan Zhu; Chengzhang Wang; Hao Sun (Plant Molecular Biology Reporter, 2026)

Synergistic hydroxyl and chlorine radicals in contact-electro-catalysis for sustainable PFAS remediation - Jin Zhang; Wei Li; Jinxing Ma; Jianghu Cui; Kuanchang He; Kui Yang; Qian Liu; Min Zhang; Sihao Lv; Faliang Cheng; Defeng Xing (Journal of Hazardous Materials, 2026)

Reutilization of digestate (residue and liquid) in the anaerobic digestion of sole corn stover: biochar preparation, methane performance and microbial responses - Haipeng Wang; Hao Sun; Sheng-Nan Zhuo; Jianrui Li; Zetang Chai; Jingwen Jia; Guangli Cao; Guo-Jun Xie; Defeng Xing; Nan-Qi Ren; Bing-Feng Liu (Journal of Environmental Management, 2026)

Electrically enhanced microalgae-bacteria systems for wastewater treatment under low-temperature conditions - Qitong Cai; Zhengpeng Wang; Xinyu Li; Yan Liu; Nanqi Ren; Defeng Xing; Xiaoxue Mei; Yawen Fan (Bioresource Technology, 2026)

Heterostructured composite cathodes with negative thermal expansion properties for enhancing IT-SOFCs electrochemical performance and durability - Jiahui Zhu; Yu Cheng; Xiaofei Zhu; Ling Hu; Shangyu Li; Defeng Zhou; Jinghe Bai (Chemical Engineering Journal, 2026)

Chlorocholine chloride delays progenitor Leydig cell differentiation via PI3K/AKT pathway activation in rats - Haoran Zhang; Yijia Li; Xiaoxia Wang; Chenping Kang; Qiong Zhang; Defeng Liu; Jiaming Mao; Qianqian Xiao; Weidong Hao (Toxicology, 2026)

Analysis of the Molecular Mechanism of Flavonoid Responses in the Medicinal Plant Paeonia lactiflora to Flower Bud Removal - Wenle Wang; Defeng Zhuang; Hui Li; Feibiao Shan; Junying Jia; Minhui Li (Journal of Plant Growth Regulation, 2026)

Collision avoidance for maritime autonomous surface ship in busy waterways based on the improved deep reinforcement learning and K-means clustering - Hui Yu; Defeng Wu; Guoqiang Li; Te Lian; Yuqin Li; Fusheng Li (Ocean Engineering, 2026)

Rare Bacterial Taxa Drive Soil Multifunctionality in Lakeside Wetlands of Eutrophic Lake - Lingchen Yuan; Jiajia Zhang; Mengxi Gao; Renlei Yang; Yue Chen; Bin Hu; Defeng Feng; Wei Li (Wetlands, 2026)

Flume investigation of the breach process of rock-avalanche dam characterized by a coarse carapace layer - Tingkai Nian; Dongyang Li; Hao Wu; Rundong Zhao; Defeng Zheng (Natural Hazards, 2026)

Physiological stress and tissue damage response of Ctenopharyngodon idella to artificial and automated injection - Lin Luo; Zhen Qin; Chen Li; Defeng Zhang; Yan Ren; Qing Wang; Chenqing Zhang; Songming Zhu; Zhangying Ye (Aquaculture International, 2025)

Memory-based deep reinforcement learning for COLREGs-compliant obstacle avoidance in USV with limited environmental knowledge - Zhenhong Fan; Defeng Wu; Yuqin Li; Zheng You; Shangkun Zhong (Ocean Engineering, 2025)

Enhancing E. coli removal in mesophilic anaerobic digestion: New insights from inoculum comparison and metagenomic analysis - Haipeng Wang; Zetang Chai; Jianrui Li; Hao Sun; Hong-Yu Ren; Guangli Cao; Guo-Jun Xie; Defeng Xing; Nan-Qi Ren; Bing-Feng Liu (Bioresource Technology, 2025)

Krϋppel-like factor 12a and 12b inhibit Cyvirus cyprinidallo3 replication by repressing viral ORF8 promoter activity - Xinyue Hu; Yingying Li; Yingying Wang; Defeng Zhang; Donghai Liu; Qing Wang; Shucheng Zheng (Fish & Shellfish Immunology, 2025)

Direct ammonia oxidation colony-driven DAAO process: construction strategy and optimization of denitrification efficacy - Yuwei Mi; Dingqiu Wei; Shuangjiang Liu; Defeng Li; Han Chen; Yijie Zheng; Mingming Chen; Dongru Qiu; Renbing Bao; Jian Xu; Zhiquan Hu (Chemical Engineering Journal, 2025)

FeCN/MXene as novel heterogeneous electro-Fenton catalysts for the degradation of sulfathiazole: Performance and mechanism investigation - Huilai Liu; Zhihao Li; Defeng Kong; Xing Chen (Journal of Environmental Sciences, 2025)

Introducing transition metal cations to promote the oxygen reduction kinetics of double perovskite as SOFC cathode - Jie Yang; Yaping Zhang; Xiaofei Zhu; Jinghe Bai; Shangyu Li; Wenfu Yan; Defeng Zhou (Chemical Engineering Journal, 2025)

Landslide susceptibility assessment using AutoML-SHAP method in the southern foothills of Changbai Mountain, China - Defeng Zheng; Yuanyuan Li; Chenglin Yan; Hao Wu; Yosuke Alexandre Yamashiki; Botong Gao; Tingkai Nian (Landslides, 2025)

Dynamic collision avoidance for maritime autonomous surface ships based on deep Q-network with velocity obstacle method - Yuqin Li; Defeng Wu; Hongdong Wang; Jiankun Lou (Ocean Engineering, 2025)

Designing and evaluating a novel blood-brain barrier in vitro model of teleost for reproducing alterations in brain infecting - Yanghui Chen; Yi Li; Wenze Li; Yuan Li; Defeng Zhang; Yu Huang; Jia Cai; Eakapol Wangkahart; Jichang Jian; Bei Wang (Fish & Shellfish Immunology, 2025)

Integrated transcriptome and metabolome profiles reveal the regulatory molecular mechanisms of meat quality in pasture-fed goose - Qasim Ali; Boshuai Liu; Shaokai La; Umar Farooq; Yao Han; Mengqi Liu; Yan Zhang; Defeng Li; Zhichang Wang; Hao Sun; Yalei Cui; Sen Ma; et al. (Food Bioscience, 2024)

Fluorocarbon polymers mediated contact-electro-catalysis activating peroxymonosulfate for emerging pollutants degradation: The key role of fluorine density in electron transfer - Dongmei Ma; Wei Li; Jin Zhang; Kuanchang He; Changyong Zhang; Gang Wang; Xiaodong Xin; Qian Liu; Faliang Cheng; Sihao Lv; Defeng Xing (Chemical Engineering Journal, 2024)

Bonding characteristics between existing concrete substrate and high ductility geopolymer overlays under direct shear loading - Shan Li; Wentao Ma; Defeng Chen; Yiyan Lu; Zhenzhen Liu (Engineering Structures, 2024)

Chitin nanocrystals-stabilized emulsion as template for fabricating injectable suspension containing polylactide hollow microspheres - Sumin Yu; Guangni Peng; Jiali Jiao; Peng Liu; Huajun Li; Juqun Xi; Defeng Wu (Carbohydrate Polymers, 2024)

Development of real‐time recombinase polymerase amplification ( RPA ) and RPA combined with lateral flow dipstick ( LFD ) assays for the rapid and sensitive detection of cyprinid herpesvirus 3 - Yingying Li; Ruifan Li; Xubing Mo; Yingying Wang; Jiyuan Yin; Sven M. Bergmann; Yan Ren; Houjun Pan; Cunbin Shi; Defeng Zhang; Qing Wang (Journal of Fish Diseases, 2024)
In this issue, we established rapid, cost‐effective, and simple detection methods including recombines polymerase amplification with lateral flow dipstick (RPA‐LFD) and real‐time RPA for cyprinid herpesvirus 3(CyHV‐3), and evaluated their sensitivity, specificity, and applicability, the real‐time RPA method could achieve sensitive diagnosis of CyHV‐3 within 1.3 copies per reaction, respectively. The real‐time RPA method is 10‐fold more sensitive than RPA‐LFD method. The exact number of CyHV‐3 can be calculated in each sample by real‐time RPA. The sera from koi also can be tested in these methods. In addition, no cross‐reaction was observed with other related pathogens, including carp oedema virus (CEV), spring viraemia of carp virus (SVCV), cyprinid herpesvirus 1(CyHV‐1), cyprinid herpesvirus 2(CyHV‐2), type I grass carp reovirus (GCRV‐I), type II GCRV (GCRV‐II), type III GCRV (GCRV‐III), and Aeromonas hydrophila.

A hydrogel-modified electrochemical biosensor for the rapid detection of ammonia‑nitrogen-resistant bacteria - Ting Zhang; Sayeda A. Abdelhamid; Defeng Li; Houjin Zhang (Science of The Total Environment, 2024)

Overlooked in-situ sulfur disproportionation fuels dissimilatory nitrate reduction to ammonium in sulfur-based system: Novel insight of nitrogen recovery - Bo Shao; Li Niu; Yuan-Guo Xie; Ruochen Zhang; Wei Wang; Xijun Xu; Jianxing Sun; Defeng Xing; Duu-Jong Lee; Nanqi Ren; Zheng-Shuang Hua; Chuan Chen (Water Research, 2024)

Underactuated MSV path following control via stable adversarial inverse reinforcement learning - Lingyu Li; Yong Ma; Defeng Wu (Ocean Engineering, 2024)

Water-saving irrigation and delayed sowing increased the emission intensity of CH4 and N2O in the rice-wheat rotated field under nighttime warming - Yunsheng Lou; Jun Li; Junhong Guo; Defeng Pan; Zhen Zhang; Li Ma; Rui Li; Lixuan Ren (Agriculture, Ecosystems & Environment, 2024)

Coxsackievirus and adenovirus receptor inhibits tilapia lake virus infection via binding to viral segment 8 and 10 encoded protein - Jing Wen; Zishan Ke; Yingying Wang; Yingying Li; Defeng Zhang; Xubing Mo; Jiyuan Yin; Cunbin Shi; Wenli Zhou; Shucheng Zheng; Qing Wang (Fish & Shellfish Immunology, 2024)

A novel study of brain microvascular endothelial cells induced by astrocyte conditioned medium for constructing blood brain barrier model in vitro: A promising tool for meningitis of teleost - Yanghui Chen; Yuan Li; Junliang Luo; Zixin Li; Yu Huang; Jia Cai; Dongneng Jiang; Defeng Zhang; Jichang Jian; Jun Qiang; Bei Wang (Fish & Shellfish Immunology, 2024)

Preparation of PCL/lecithin/bacteriocin CAMT6 antimicrobial and antioxidant nanofiber films using emulsion electrospinning: Characteristics and application in chilled salmon preservation - Qibin Li; Weiqi Liang; Linao Lv; Zhijia Fang; Defeng Xu; Jianmeng Liao; Ying Liu (Food Research International, 2024)

Carbon-based materials as highly efficient catalysts for the hydrogen evolution reaction in microbial electrolysis cells: Mechanisms, methods, and perspectives - Lina Xu; Wei Li; Jiaqin Luo; Lingyu Chen; Kuanchang He; Dongmei Ma; Sihao Lv; Defeng Xing (Chemical Engineering Journal, 2023)

Effects of long-term warming on soil prokaryotic communities in shrub and alpine meadows on the eastern edge of the Qinghai-Tibetan Plateau - Wei Li; Lingchen Yuan; Xianli Lan; Rui Shi; Dongdong Chen; Defeng Feng; Xinquan Zhao; Huai Chen (Applied Soil Ecology, 2023)

Hexavalent chromium disrupts the skin barrier by targeting ROS-mediated mitochondrial pathway apoptosis in keratinocytes - Cheng Wang; Hongqi Shang; Shuyu Zhang; Xiangkun Wang; Defeng Liu; Mingyue Shen; Ning Li; Yunxuan Jiang; Kai Wei; Ruiliang Zhu (Chemico-Biological Interactions, 2023)

Pathogenicity of duck circovirus and fowl adenovirus serotype 4 co-infection in Cherry Valley ducks - Mingyue Shen; Panpan Gao; Cheng Wang; Ning Li; Shuyu Zhang; Yunxuan Jiang; Defeng Liu; Baoyu Jia; Li Xu; Bohan Huang; Ruiliang Zhu; Kai Wei (Veterinary Microbiology, 2023)

Proximal policy optimization with reciprocal velocity obstacle based collision avoidance path planning for multi-unmanned surface vehicles - Delai Xue; Defeng Wu; Andre S. Yamashita; Zhixiong Li (Ocean Engineering, 2023)

Conductive carrier promotes synchronous biofilm formation and granulation of anammox bacteria - Kun Feng; Yu Lou; Yitian Li; Baiyun Lu; Anran Fang; Guojun Xie; Chuan Chen; Defeng Xing (Journal of Hazardous Materials, 2023)

Comparative genomics studies on the stk gene family in vertebrates: From the bighead carp (Hypophthalmichthys nobilis) genome - Yang Mao; Defeng Li; Rongrong Chen; Caifeng Ma; Junzhi Xiong; Kebin Zhang (Fish & Shellfish Immunology, 2023)

A New Conditionally Immortalized Nile Tilapia (Oreochromis niloticus) Heart Cell Line: Establishment and Functional Characterization as a Promising Tool for Tilapia Myocarditis Studies - Yanghui Chen; Yuan Li; Dongneng Jiang; Defeng Zhang; Yu Huang; Jia Cai; Jichang Jian; Bei Wang (Fishes, 2023)
A new cell line named the tilapia heart cell line (TAH-11) was established from the heart of tilapia (Oreochromis niloticus) by enzymatic digestion and mechanical separation. The TAH-11 cell line has been stably subcultured for over 80 generations and resuscitated after being frozen in liquid nitrogen for six months, with exuberant cell growth. The optimal culture condition of TAH-11 is L-15 medium supplemented with 10% fetal bovine serum at 25 °C. Sequencing of the mitochondrial 18S rRNAs confirmed that TAH-11 cells were derived from the tilapia. TAH-11 was also identified as a myocardial cell line based on the mRNA expression of the troponin I, α-actin and myoglobin genes. Simultaneously, TAH-11 could be successfully transfected with the GFP reporter gene, suggesting that the TAH-11 cell line could be used for exogenous gene expression in vitro. The TAH-11 cells showed susceptibility to CGSIV, which was demonstrated by the presence of a severe cytopathic effect, suggesting that the TAH-11 cell line is an ideal tool for studying host–virus interaction and potential vaccines. In addition, the expression of inflammatory factors in TAH-11 cells can be remarkably induced following Streptococcus agalactiae or Streptococcus iniae. The present data lays a foundation to further explore the mechanism of how Streptococcus spp. causes tilapia myocarditis.

Thermophilic dark fermentation fast start-up of hydrogen production with substrate concentration regulation and moderate pretreatment inoculum - Tianming Yin; Wei Wang; Shengnan Zhuo; Guangli Cao; Hongyu Ren; Jianrui Li; Defeng Xing; Guojun Xie; Bingfeng Liu (Fuel, 2023)

Long Non-coding RNA LOXL1-AS1 Facilitates Colorectal Cancer Progression via Regulating miR-1224-5p/miR-761/HK2 Axis - Tao Guo; Shihao Peng; Defeng Liu; Yangyang Li (Biochemical Genetics, 2022)

MSINGB: A Novel Computational Method Based on NGBoost for Identifying Microsatellite Instability Status from Tumor Mutation Annotation Data - Jinxiang Chen; Miao Wang; Defeng Zhao; Fuyi Li; Hao Wu; Quanzhong Liu; Shuqin Li (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Comparative and functional analyses of fecal microbiome in Asian elephants - Guiding Li; Yi Jiang; Qinyuan Li; Defeng An; Mingwei Bao; Lei Lang; Li Han; Xueshi Huang; Chenglin Jiang (Antonie van Leeuwenhoek, 2022)

Mutations in surface‐sensing receptor WspA lock the Wsp signal transduction system into a constitutively active state - Anming Xu; Di Wang; Yunhao Wang; Li Zhang; Zhensheng Xie; Yifan Cui; Pramod Bhamse; Haiying Yu; Xue‐Xian Zhang; Defeng Li; Luyan Z. Ma (Environmental Microbiology, 2022)
Summary Pseudomonas aeruginosa rugose small‐colony variants (RSCVs) are frequently isolated from chronic infections, yet, they are rarely reported in environmental isolates. Here, during the comparative genomic analysis of two P . aeruginosa strains isolated from crude oil, we discovered a spontaneous in‐frame deletion, wspA Δ280–307 , which led to hyper‐biofilm and RSCV phenotypes. WspA is a homologue of methyl‐accepting chemotaxis proteins (MCPs) that senses surfaces to regulate biofilm formation by stimulating cyclic‐di‐guanosine monophosphate (c‐di‐GMP) synthesis through the Wsp system. However, the methylation sites of WspA have never been identified. In this study, we identified E280 and E294 of WspA as methylation sites. The wspA Δ280–307 mutation enabled the Wsp system to lock into a constitutively active state that is independent of regulation by methylation. The result is an enhanced production of c‐di‐GMP. Sequence alignment revealed three conserved repeat sequences within the amino acid residues 280–313 (aa280–313) region of WspA homologues, suggesting that a spontaneous deletion within this DNA encoding region was likely a result of intragenic recombination and that similar mutations might occur in several related bacterial genera. Our results provide a plausible explanation for the selection of RSCVs and a mechanism to confer a competitive advantage for P . aeruginosa in a crude‐oil environment.

Comparative Transcriptome Analysis of Spleen Reveals Potential Regulation of Genes and Immune Pathways Following Administration of Aeromonas salmonicida subsp. masoucida Vaccine in Atlantic Salmon (Salmo salar) - Qiang Fu; Yuqing Li; Hao Zhang; Min Cao; Lu Zhang; Chengbin Gao; Xin Cai; Defeng Chen; Ziying Yang; Jie Li; Ning Yang; Chao Li (Marine Biotechnology, 2022)

The regulatory role of dietary factors in skeletal muscle development, regeneration and function - Liyi Wang; Ziye Xu; Defeng Ling; Jie Li; Yizhen Wang; Tizhong Shan (Critical Reviews in Food Science and Nutrition, 2022)

Variations in bacterial and archaeal community structure and diversity along the soil profiles of a peatland in Southwest China - Wei Li; Mingmo Luo; Rui Shi; Defeng Feng; Zhenan Yang; Huai Chen; Bin Hu (Environmental Science and Pollution Research, 2022)

Chain pillar optimization at a longwall coal mine based on field monitoring results and numerical model analysis - Qingwen Shi; Gang Xu; Defeng Wang; Zhengjie Li; Wangrong Liu; Xiao Wang (Arabian Journal of Geosciences, 2021)

Streptococcus shenyangsis sp. nov., a New Species Isolated from the Oropharynx of a Healthy Child from Shenyang China - Defeng Liu; Chunling Xiao; Xinming Li; Ye Sun; He Qi; Yang Zou (Current Microbiology, 2021)

Falsigemmobacter faecalis gen. nov. sp. nov., isolated from faeces of Rhinopithecus roxellanae, and reclassification of Gemmobacter intermedius as Falsigemmobacter intermedius comb. nov - Guiding Li; Yi Jiang; Qinyuan Li; Xiu Chen; Longqian Jiang; Kun Zhang; Defeng An; Lei Lang; Li Han; Xueshi Huang; Chenglin Jiang (Archives of Microbiology, 2020)

Comparison of Anaerobic Methane Oxidation in Different Sediment Habitats of Dianchi Lake - Wei Li; Yue Chen; Mingmo Luo; Chunyan Li; Yonggui Zhao; Huai Chen; Defeng Feng; Bin Hu (Water, Air, & Soil Pollution, 2020)

Methylobacterium planium sp. nov., isolated from a lichen sample - Longqian Jiang; Defeng An; Xinyu Wang; Kun Zhang; Guiding Li; Lei Lang; Lisong Wang; Chenglin Jiang; Yi Jiang (Archives of Microbiology, 2020)

Soil water content and pH drive archaeal distribution patterns in sediment and soils of water-level-fluctuating zones in the East Dongting Lake wetland, China - Wei Li; Defeng Feng; Gang Yang; Zhengmiao Deng; Junpeng Rui; Huai Chen (Environmental Science and Pollution Research, 2019)

A Path-Planning Strategy for Unmanned Surface Vehicles Based on an Adaptive Hybrid Dynamic Stepsize and Target Attractive Force-RRT Algorithm - Zhen Zhang; Defeng Wu; Jiadong Gu; Fusheng Li (Journal of Marine Science and Engineering, 2019)
It is well known that path planning has always been an important study area for intelligent ships, especially for unmanned surface vehicles (USVs). Therefore, it is necessary to study the path-planning algorithm for USVs. As one of the basic algorithms for USV path planning, the rapidly-exploring random tree (RRT) is popular due to its simple structure, high speed and ease of modification. However, it also has some obvious drawbacks and problems. Designed to perfect defects of the basic RRT and improve the performance of USVs, an enhanced algorithm of path planning is proposed in this study, called the adaptive hybrid dynamic stepsize and target attractive force-RRT(AHDSTAF-RRT). The ability to pass through a narrow area and the forward speed in open areas of USVs are improved by adopting the AHDSTAF-RRT in comparison to the basic RRT algorithm. The improved algorithm is also applied to an actual gulf map for simulation experiments, and the experimental data is collected and organized. Simulation experiments show that the proposed AHDSTAF-RRT in this paper outperforms several existing RRT algorithms, both in terms of path length and calculating speed.

Regulation of Thermostable Direct Hemolysin and Biofilm Formation of Vibrio parahaemolyticus by Quorum-Sensing Genes luxM and luxS - Muhan Guo; Zhijia Fang; Lijun Sun; Dongfang Sun; Yaling Wang; Can Li; Rundong Wang; Yang Liu; Hanqiao Hu; Ying Liu; Defeng Xu; Ravi Gooneratne (Current Microbiology, 2018)

Reduced antigen presentation capability and modified inflammatory/immunosuppressive cytokine expression of induced monocyte-derived dendritic cells from peripheral blood of piglets infected with porcine circovirus type 2 - Ning Yang; Jiandong Li; Qian Yang; Jinzeng Qiao; Defeng Cui; Fenghua Liu; Huanrong Li; Shuanghai Zhou (Archives of Virology, 2018)

Tree-scale spatial variation of soil respiration and its influence factors in apple orchard in Loess Plateau - Rui Wang; Shengli Guo; Jishao Jiang; Defeng Wu; Nana Li; Yanjun Zhang; Qingfang Liu; Rujian Li; Zhiqi Wang; Qiqi Sun; Lanlan Du; Man Zhao (Nutrient Cycling in Agroecosystems, 2015)

Differential expression of the Toll-like receptor pathway and related genes of chicken bursa after experimental infection with infectious bursa disease virus - Xinfeng Guo; Liqiong Wang; Defeng Cui; Wenke Ruan; Fenghua Liu; Huanrong Li (Archives of Virology, 2012)

Identification of a Toll-Like Receptor 1 in Guinea Fowl (Agelastes niger) - Yanhua Wu; Wenke Ruan; Defeng Cui; Huanrong Li (Biochemical Genetics, 2012)